Incidence of dispensing errors before and after root cause analysis at Sanglah General Hospital, Denpasar - Ni Kadek Erna Erawati; I Made Ady Wirawan; Cokorda Bagus Jaya Lesmana (Universitas Udayana, 2019)
Background and purpose: Drug dispensing errors have a major impact on the incidence of medication errors, and can be very dangerous to patients and affect the quality of care. Root cause analysis (RCA) is an approach to prevent dispensing errors by identifying the root of the problem, make efforts to improve comprehensively across departments so that incidence of dispensing errors are not repeated. The purpose of this study is to determine the differences in the incidence of dispensing errors before and after the RCA. Methods: This is a descriptive study by calculating the incidence of dispensing errors before and after the RCA, conducted in four inpatient wards at Sanglah Hospital Denpasar. Dispensing errors were categorized into ten types namely errors in drug’s identity, name, dosage, number of drugs, absence of high alert labels, incorrect drug preparations, incorrect strength, expired drugs, incorrect place of delivery and incorrect instructions. In February and April 2018 there were 80 and 40 dispensing errors which met the study criteria, respectively. Results: Crude incidence of dispensing errors before and after RCA were 2.54 per 1000 (95%CI: 1.98-3.10) and 1.26 per 1000 (95%CI: 0.87-1.65), respectively. The decrease in dispensing error after RCA was 50.39%. The ratio of dispensing error incidence rates after and before the RCA is 0.49. Significant decrease in the incidence of dispensing errors was only found in drug identity errors of 1.27 per 1000 (95%CI: 0.88-1.66) before an RCA and 0.06 per 1000 (95%CI: -0.03-0.15) after RCA, or decreased by 95.27% and there was no significant decrease in other dispensing errors. Conclusion: The decrease of dispensing errors after the RCA was only found in the medication identity error and not found in the other dispensing errors. Direct observation and intensive supervision are needed in order to accurately calculate and reduce the incidence of dispensing errors.